The use of modified Montgomery T-tubes as frontal sinus stents: how I do it. Issue 12 (31st December 2022) - Bandino, F; Bates, J; Qureishi, A; Martinez-Devesa, P
Abstract: Background: Frontal sinus surgery is challenging as the frontal recess is prone to re-stenosis and there is subsequent occlusion of the frontal sinus outflow tract. In an attempt to maintain the frontal recess calibre and reduce frontal sinus re-stenosis, frontal sinus stents have been used with different materials and varying results. Objective: This paper presents the technique of using a modified Montgomery T-tube as a frontal sinus stent. Results and conclusion: The use of a soft, self-retaining and non-absorbable stent that can be used for stenting of the frontal sinus is described. Our technique is safe, effective, inexpensive and well tolerated.